2011
DOI: 10.1097/jsm.0b013e318219a649
|View full text |Cite
|
Sign up to set email alerts
|

Survey Study of Members of the Canadian Orthopaedic Association on the Natural History and Treatment of Anterior Cruciate Ligament Injury

Abstract: In the rapidly evolving area of ACL reconstruction, no recent surveys of opinions and preferences of Canadian orthopedic surgeons have been published. In addition to providing information from a Canadian perspective, the findings from this study will allow surgeons to evaluate a range of treatment decisions based on the general opinions of their colleagues and also highlights areas of dissimilarity that can be targeted for more extensive research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 20 publications
5
54
2
Order By: Relevance
“…Similar studies by McRae et al (2011) and Chechik et al (2013) reported preferences for the STG autograft as 73% and 63% respectively, which is considerably lower than the findings of the current study. Unfortunately, it is not clear from the results why such a bias towards the STG autograft was identified among the sample population.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Similar studies by McRae et al (2011) and Chechik et al (2013) reported preferences for the STG autograft as 73% and 63% respectively, which is considerably lower than the findings of the current study. Unfortunately, it is not clear from the results why such a bias towards the STG autograft was identified among the sample population.…”
Section: Discussioncontrasting
confidence: 72%
“…Eleven studies were identified that conducted a survey primarily related to ACLR surgical practice, however, of the 11 studies identified, only one included a specific question on graft tension (McRae, Chahal, Leiter, Marx, & MacDonald, 2011). This study investigated the method of tensioning; however, did not explore other factors such as the amount of tension or the rationale for graft tensioning (McRae et al, 2011).…”
Section: Literature Review To Identify a Relevant Valid And Reliable mentioning
confidence: 99%
See 1 more Smart Citation
“…Enabling return to competitive sport is a common reason for performing ACLR and most individuals electing to undergo surgery expect to return to pre-injury sport within one year (Feucht et al, 2014;Marx et al, 2003;McRae et al, 2011). Of concern is that more than 50% of non-elite sports participants do not return to pre-injury sport after ACLR (Ardern et al, 2014b), which was a critical determinant of longer-term QOL 5 to 20 years after ACLR in people with knee difficulties (Chapter 6).…”
Section: Return To Sportmentioning
confidence: 99%
“…Rationales for performing an ACLR include facilitating a return to competitive sport (Marx et al, 2003;McRae, Chahal, Leiter, Marx, & MacDonald, 2011) and minimising the risk of post-traumatic knee osteoarthritis (Richmond et al, 2011). However, many ACLreconstructed individuals cease sports participation (Ardern et al, 2014b), develop accelerated knee osteoarthritis (Øiestad et al, 2009), or experience ongoing fear of re-injury (Ardern et al, 2012a) and poor knee-related QOL (Chapter 4).…”
Section: Introductionmentioning
confidence: 99%